The Concept of Arabic Language Development in Early Childhood - Anwar Zain (Tajdid Al-Athfal, 2021)
Children are stimulated in various ways of being active and active so that their potential in language can be maximized. Therefore, the AUD Language Development course at tertiary institutions in the PAUD Study Program provides expertise in these courses. The development of Arabic in early childhood is very important to be introduced in the learning process. The research method uses literature study with a qualitative descriptive approach to produce concepts and opinions from in-depth analysis through data collection, data reduction, data presentation and conclusions comprehensively. The results of this concept study study state that learning and introduction to Arabic is very important because it is a tool for children to familiarize themselves with carrying out religious teaching activities using Arabic reading, such as praying, praying, reading al-qur'an, hadith, dzikir and other religious worship. Learning Arabic in early childhood education is only pronunciation, while learning Arabic at secondary school (adult children) is rules (qawaid) in Arabic. Methods in introducing Arabic to children through songs, conversations / chants, daily prayers, religious worship, reading al-qur'an and hadith, objects, pictures, calculations, and activities, as well as through video